Contrôlabilité d'un dispositif mobile via WhatsApp : amélioration des performances des apprenants - Benjamin Nkwanui; Séverine Colinet; Pascale Haag (Centre National d'Enseignement à Distance, 2021)
This paper derives from a study carried out in a thesis on effects of pedagogic differentiation in mobile learning. The approach embeds in the fact that performance depends on the controllability of the techno-differentiated device by learners (Viau, 1994, p. 7). We wanted to find out if learners are going to perform better, if they would be in control of their mobile learning environment mediated by WhatsApp. An experimentation took place during six weeks in a year 4 class of 60 students of government technical high school Yaoundé 2. We could distinguish 47 learners of the face-to-face modality, to 13 others in blended learning through WhatsApp. Controllability could be evident by the presence of utility, usability and social rules factors (O'Malley, 2005, p. 36 et 37). Radar charts presented satisfactory scores obtained by techno-differentiated learners to evaluations administered before, during and at the end of the course. The ANOVA revealed that technology users obtained better performances. These results confirmed the controllability of mobile learning devices and the increase in performance with the use of WhatsApp. We concluded that such a differentiated setting is effective in the context of schools that find it tedious to acquire devices that are more sophisticated.